Unveiling Burnout: How Psychological Well-Being and Quality of Life Shape Female Lecturers' Resilience - Ambarsarie, Riry; Dinda, Rofifah; Saki, Vernonia Yora; Euleryn, Norevia; Ashan, Hesty Rhauda (Fakultas Kedokteran Universitas Riau, 2025)
Female lecturers are more vulnerable to burnout due to biological and emotional factors, as well as the dual roles they often manage. Psychological well-being (PWB) and quality of life (QOL) are critical factors that can influence the occurrence of burnout. This research aims to determine the relationship between PWB and QOL with the level of burnout syndrome among female lecturers at University of Bengkulu. This study employed an observational cross-sectional design, consisted of 86 female lecturers at the University of Bengkulu selected through stratified random sampling. The variables were assessed by using Ryff’s Psychological Well-Being Scale, WHOQOL-BREF questionnaire, and Maslach Burnout Inventory Educators Survey. Data were analyzed using univariate, bivariate and multivariate analysis. The results showed that the majority of respondents were aged 36-45 years (34.9%), married (83.7%), and held a Master's degree (68.6%), have a high PWB level (86%) with good QOL (58.1%) and have a mild burnout syndrome (91.9%). The Pearson chi-square test analysis results show p = 0.0001 (p ≤ 0.05) for both PWB and QOL. From the multiple linear regression analysis, it was found that both the PWB and QOL variables have a negative and significant effect on burnout syndrome among female lecturers. Each increase both PWB and QOL will reduces burnout by 0.255 (PWB) and 0.829 (QOL). With appropriate interventions, it is hoped that a healthier and more productive work environment can be created, supporting professional development and the emotional well-being of educators, especially with female lecturers.